Pengaruh Transformational Leadership Pada Kinerja Pegawai dengan Kompensasi dan Kepuasan Kerja Sebagai Variabel Mediasi - Puspitaria, Ika; Hendarsjah, Hidajat (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to scrutinize the effect of transformational leadership on employee performance with compensation and job satisfaction as mediating variables. The research results are expected will inspire managers to prepare transformational leadership steps and strategies to improve employee performance and develop employees. The research was conducted on the regional apparatus in the Madiun City Government, with a sample of 327 respondents. The approach in this study used a quantitative approach, with data collection methods using primary and secondary data. The reliability test employed Cronbach Alpha, while the validity test utilized convergent validity and discriminant validity. Another test used Ordinary Least Squares (OLS) regression analysis. The results uncovered that (1) transformational leadership had a positive association with compensation; (2) Transformational leadership had no positive association with job satisfaction; (3) Transformational leadership positively associated with employee performance; (4) Compensation had a positive association with employee performance; (5) Job satisfaction had a positive association with employee performance; (6) There was a positive association between transformational leadership and employee performance, with compensation as a mediating variable. In addition, (7) there was a positive association between transformational leadership and employee performance, with the mediating variable of job satisfaction. There was a positive association between compensation and job satisfaction as a mediating variabel in the relationship between transformational leadership and employee performance. Keywords: compensation, employee performance, job satisfaction, transformational leadership